Diurnal increases in depths of humpback whale (Megaptera novaeangliae) mother‐calf pods off West Maui, Hawaiʻi: A response to vessels? - Pack, Adam A.; Waterman, James O.; Craig, Alison S. (Marine Mammal Science, 2022)
Studies of humpback whale (Megaptera novaeangliae) habitat use in their Hawaiian breeding grounds have revealed that mother-calf pairs favor shallow waters to avoid harassment from males. However, human activity in these same waters may exert an opposing force on habitat use. To investigate this hypothesis, instantaneous scan samples of whale and vessel distribution were collected from West Maui, Hawaiʻi. Theodolite position fixes were combined with GIS techniques to determine the depths and seabed terrain type occupied by 161 humpback whale pods containing a calf (calf pods) and 872 pods without a calf (noncalf pods). We found no significant diurnal trends for noncalf pods, but calf pods occupied progressively deeper water over the course of each day. There was no evidence that this shift was related to (1) a “spillover” resulting from high mother-calf density in shallow water, (2) harassment by males occupying the same space as mother-calf pairs, or (3) the presence of mainly older and larger calves. However, while diurnal trends of whale-watching vessels largely mirrored those of mother-calf pods, nonwhale-watching vessels tended to remain in shallower waters throughout the day. These results suggest that nearshore vessels may negatively impact the natural preference of mother-calf pairs for shallow waters.